Kesenjangan Pengetahuan, Sikap, dan Praktik (KAP) Pencegahan DBD di Wilayah Kerja Puskesmas Cakranegara: Diagnosis Komunitas - Nisia Putri Rinayu; Irwan Syuhada; Ni Made Dwita Wiwahani; Ahmad Tristan Amartya; Baiq Fahira Mentari (SEHATMAS: Jurnal Ilmiah Kesehatan Masyarakat, 2025)
Dengue remains a major public health concern in Indonesia. In 2024, the incidence rate (IR) more than doubled (91.1) versus 2023 (41.4), while the case fatality rate (CFR) fell from 0.96% to 0.57%, underscoring the need to shift from curative care to community-based prevention. This descriptive observational study using a community-diagnosis approach assessed knowledge, attitudes, and practices (KAP) for dengue prevention and household environmental conditions in RT 6 Selagalas Lama. The target population comprised 153 households; 60 respondents were selected with Slovin’s formula (10% margin of error). Data were collected via a KAP questionnaire and household environmental observations and analyzed descriptively (univariate). Most respondents showed good knowledge (86.7%) and positive attitudes (86.7%), yet preventive practices were suboptimal (good 28.3%; fair 35.0%; poor 36.7%). Household environments were predominantly poor (70.0%), with key misconceptions persisting (43.3% cited Anopheles as the vector; 46.7% believed dengue cannot be prevented). To address the K–A–P gap, we implemented hands-on, demonstration-based “3M Plus” education focused on weekly self-inspection of water-holding containers and improved personal protection (morning–afternoon protection; window/door screens and bed nets). The knowledge/attitude–practice gap remains a primary local risk; structured, measurable, demonstration-based interventions should be institutionalized and evaluated using practice indicators, vector indices, and clinical outcomes.